Foliar application of sodium selenite affects the growth, antioxidant system, and fruit quality of strawberry - Lin, Yuanxiu; Cao, Shuaipeng; Wang, Xiao; Liu, Yin; Sun, Ziqing; Zhang, Yunting; Li, Mengyao; Wang, Yan; He, Wen; Zhang, Yong; Chen, Qing; Wang, Xiaorong; et al. (Frontiers in Plant Science, 2024)
Selenium (Se) plays a vital role in various physiological processes in plants, it is regarded as an essential micronutrient for human health as well. In this study, sodium selenite solution at 10, 40, 70, and 100 mg•L -1 concentrations was foliar sprayed, and the strawberry plant growth, antioxidant system and fruit quality with an emphasis on sugar and acid content were assessed. The results showed that 10 mg•L -1 of sodium selenite treatment apparently promoted the plant growth, while all the treated concentrations could enhance photosynthesis, antioxidant system in leaves, the content of Se and ascorbic acid in fruits. More importantly, 40 mg•L -1 sodium selenite treatment significantly increased fruit weight, total soluble solid, and total phenolic content, anthocyanins, as well as improved the shape index. Whereas, it decreased the total flavonoid and proanthocyanidins content. Particularly, sodium selenite treatment at 40 and 70 mg•L -1 largely increased the ratio of soluble sugars to titratable acid. The changes of predominant sugars and organic acids during fruit development were further investigated. The sucrose, fructose and glucose content was upregulated by sodium selenite treatment through upregulating the activities of sucrose phosphate synthase (SPS) and acid invertase, as well as the FaSPS expression. In addition, sodium selenite treatment inhibited the activity of citrate synthase and phosphoenol pyruvate carboxylase, rather than modulating their transcript levels to reduce the citric acid content. This work presented a potentially efficient approach to enhance plant growth and fruit quality and supplement Se in strawberry, providing insights into the mechanism of regulating sugar and acid metabolism by Se.